2020
DOI: 10.26605/medvet-v14n4-2371
|View full text |Cite
|
Sign up to set email alerts
|

Detection of anti-Neospora caninum antibodies in slaughtered sheep

Abstract: Neospora caninum is a protozoan that causes reproductive disorders in herbivores. Domestic and wild dogs have been considered its definitive hosts, and when these animals are affected, they may suffer from a neuromuscular disease. Recently, this infection has also gained significance in small ruminants. Although neosporosis is already a proven cause of mortality in lambs and congenital infection can occur, this parasite has only recently been considered a cause of abortion in these animals. The aim of this stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 17 publications
1
1
0
Order By: Relevance
“…In sheep, the seroprevalence found in this study was above 12%, remaining within the seroprevalence range described in studies from different states and regions of Brazil, ranging from 1.8% (Soares et al, 2009) to 64.2% (Tembue et al, 2011). The result of the present study corroborates the data found by Mendonça et al (2019) in the state of Sergipe, who obtained seropositivity of 12.4% and by Nunes et al (2020) with 13% seroprevalence in the state of Alagoas, both in the Northeast region. Despite the similarity of these seroprevalences, Moraes et al (2011) in the state of Maranhão found seroprevalence of 4.69% in sheep and Tembue et al (2011) found a seroprevalence of 64.2% in sheep from the state of Pernambuco, both in Northeast region which demonstrate a high divergence in states from the same region where the climatic conditions are similar.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In sheep, the seroprevalence found in this study was above 12%, remaining within the seroprevalence range described in studies from different states and regions of Brazil, ranging from 1.8% (Soares et al, 2009) to 64.2% (Tembue et al, 2011). The result of the present study corroborates the data found by Mendonça et al (2019) in the state of Sergipe, who obtained seropositivity of 12.4% and by Nunes et al (2020) with 13% seroprevalence in the state of Alagoas, both in the Northeast region. Despite the similarity of these seroprevalences, Moraes et al (2011) in the state of Maranhão found seroprevalence of 4.69% in sheep and Tembue et al (2011) found a seroprevalence of 64.2% in sheep from the state of Pernambuco, both in Northeast region which demonstrate a high divergence in states from the same region where the climatic conditions are similar.…”
Section: Discussionsupporting
confidence: 90%
“…These data illustrate a significant divergence from the findings presented in this study and others conducted in Brazil. It is important to acknowledge that variations between epidemiological studies can be attributed to several factors, including the inherent climatic conditions of the studied regions, the age of animals, the size of herds, the types of management practices, and variations in laboratory procedures such as evaluation methods, cutoff points used, the experience of the evaluator, and equipment maintenance (Dubey et al, 2007;Nunes et al, 2020).…”
Section: Discussionmentioning
confidence: 99%